Reaction Mechanisms of Acid-Catalyzed Hydrothermal Decomposition of Glucose and Fructose - Wu, Zhiliang (Curtin University, 2022)
This PhD study investigates the glucose and fructose hydrothermal decomposition under acid catalytic conditions, providing an in-deep understanding of reaction mechanisms, especially 5-hydroxymethylfurfural formation mechanism during sugar decomposition. Furthermore, the study indicates that the incorporation of N in acid catalysts can significantly enhance 5-HMF yield by reducing side reactions during fructose decomposition. Lastly, waste tire char (WTC) was prepared to catalyze glucose isomerization, which opens a new route to the application of WTC in biorefinery.